Craig on Atonement - Crisp, Oliver (Philosophia Christi, 2025)
In this response paper I consider two issues that relate to Craig's response to my own work on atonement, and which are, I think, at the heart of much recent criticism of penal substitution. The first has to do with the forensic or legal fiction that is part and parcel of many traditional accounts of penal substitution. The second has to do with the attempt to construct a version of penal substitution that takes seriously the sort of metaphysical realism that appears to be at work in Pauline theology, and especially in the "Adam Christology" of Romans 5:12-19. I will argue that in each case Craig's objections can be challenged, and that failure to take these matters with sufficient seriousness represents a shortcoming in his articulation of penal substitution. I close with some remarks about the contribution of Craig’s volume in the larger contemporary theological discussion of the doctrine of atonement.